Exploring Ethnomathematics in Traditional Dance Movements: A Study of the Sigeh Penguten Dance of Lampung, Indonesia - Desmawati, Riana; Nurhayati, Titik; Ulbana, Fatimatuz Zahro; Jayaningrat, Raden Hari W (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine ethnomathematics activities and mathematical concepts applied in various Sigeh Pengeten dance movements. Methodology: The type of research used in this study is qualitative research with an ethnographic approach. Data were obtained through interviews, observation, and documentation. The research instruments consisted of the primary instrument, the researcher herself, and supporting instruments in the form of interview guidelines, observation sheets, and documentation tools. Method and source triangulation were used to validate the data. Main Findings: The results of this study indicate that in each sigeh penguten dance movement, counting activities are implemented by adjusting the fast or slow music beat in the form of a repetition of 1 x 8 counts. Some sigeh penguten dance movements implement measuring activities when the movement moves to adjust to the next floor pattern change. The concept of one-dimensional geometry is depicted from the movement that forms a straight line floor pattern. The concept of two-dimensional geometry is depicted from the shape of the floor pattern in the form of triangles, rectangles, squares, trapezoids, and circles. Reflection and rotation geometric transformations. The conclusion of this study is that in the sigeh penguten dance movements there are mathematical activities and mathematical concepts. Novelty/Originality of this study: This research can be used as input for educators to make ethnomathematics an alternative in the mathematics learning process, so that it can help improve learning outcomes and students' interest in mathematics learning.